Activated platelets release sphingosine 1-phosphate and induce hypersensitivity to noxious heat stimuli in vivo - Weth, Daniela; Benetti, Camilla; Rauch, Caroline; Gstraunthaler, Gerhard; Schmidt, Helmut; Geisslinger, Gerd; Sabbadini, Roger; Proia, Richard L.; Kress, Michaela (Frontiers in Neuroscience, 2015)
At the site of injury activated platelets release various mediators, one of which is sphingosine 1-phosphate (S1P). It was the aim of this study to explore whether activated human platelets had a pronociceptive effect in an in vivo mouse model and whether this effect was based on the release of S1P and subsequent activation of neuronal S1P receptors 1 or 3. Human platelets were prepared in different concentrations (105/µl, 106/µl, 107/µl) and assessed in mice with different genetic backgrounds (WT, S1P1fl/fl, SNS-S1P1-/-, S1P3-/-). Intracutaneous injections of activated human platelets induced a significant, dose-dependent hypersensitivity to noxious thermal stimulation. The degree of heat hypersensitivity correlated with the platelet concentration as well as the platelet S1P content and the amount of S1P released upon platelet activation as measured with LC MS/MS. Despite the significant correlations between S1P and platelet count, no difference in paw withdrawal latency (PWL) was observed in mice with a global null mutation of the S1P3 receptor or a conditional deletion of the S1P1 receptor in nociceptive primary afferents. Furthermore, neutralisation of S1P with a selective anti-S1P antibody did not abolish platelet induced heat hypersensitivity. Our results suggest that activated platelets release S1P and induce heat hypersensitivity in vivo. However, the platelet induced heat hypersensitivity was caused by mediators other than S1P.